The expression of a hunchback ortholog in the polychaete annelid Platynereis dumerilii suggests an ancestral role in mesoderm development and neurogenesis - Kerner, Pierre; Arendt, Detlev (Development genes and evolution, 2006)
Orthologs of the Drosophila gap gene hunchback have been isolated so far only in protostomes. Phylogenetic analysis of recently available genomic data allowed us to confirm that hunchback genes are widely found in protostomes (both lophotrochozoans and ecdysozoans). In contrast, no unequivocal hunchback gene can be found in the genomes of deuterostomes and non-bilaterians. We cloned hunchback in the marine polychaete annelid Platynereis dumerilii and analysed its expression during development. In this species, hunchback displays an expression pattern indicative of a role in mesoderm formation and neurogenesis, and similar to the expression found for hunchback genes in arthropods. These data suggest altogether that these functions are ancestral to protostomes.